Studi Etnomatematika: Eksplorasi Konsep Bangun Datar pada Rumah Adat Balla Lompoa - Talib, Ahmad; Hamin, Muhammad Nur Ihsan; Rosadi, Muhammad Taufiq; Sari, Rolita Maya (Faculty of Tarbiyah and Teacher Training, 2025)
Mathematics as a universal science has long been a part of human life, including in aspects of culture and architecture, as found in the architecture and artifacts of the Balla Lompoa traditional house in South Sulawesi. This study aims to reveal the concept of mathematics, especially in the material of flat geometry, as well as the cultural values contained in the architecture and artifacts of the Balla Lompoa traditional house in South Sulawesi. This type of research is qualitative research with an ethnomathematics approach. Data collection techniques used are observation, interviews, and documentation. This study applies technical triangulation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the Balla Lompoa traditional house in Gowa Regency, South Sulawesi, has various flat geometry concepts that are integrated into its architecture and artifacts. Elements such as squares, rectangles, equilateral triangles, isosceles triangles, circles, trapezoids, and rhombuses are found in various elements of traditional buildings and artifacts. In addition to the mathematical aspect, this house also has strong philosophical and cultural values, reflecting the social structure and beliefs of the Gowa people. The implications of this study are that it not only enriches ethnomathematics literature but also contributes to a culture-based mathematics learning approach, which can improve students' understanding and interest in geometry material through local cultural contextualization.